2018
DOI: 10.1088/1674-1056/27/12/127805
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of indium-composition fluctuations in InGaN epitaxial layers by periodically-pulsed mixture of N 2 and H 2 carrier gas

Abstract: Indium-composition fluctuations in InGaN epitaxial layers are suppressed by using periodically-pulsed mixture (PPM) of N 2 and H 2 carrier gas. Photoluminescence, optical transmission, reciprocal space map and space-resolved cathodoluminescence are employed to characterize the InGaN epilayers. It is shown that the lateral In-fluctuations mainly occur as hillock-like In-rich regions. Both the number and size of In-rich regions are reduced by introducing the PPM carrier gas. Moreover, the measurements first expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Both in vivo and in vitro experiments have demonstrated that CircFAM160A2 regulates chondrocyte mitochondrial stability and chondrocyte apoptosis through the miR-505-3p/SIRT3 axis (Bao et al, 2021). Recent studies have also that CircHIPK3, through the mir-30a-3p/PON2 axis, regulates mitochondrial function, which in turn affects chondrocyte apoptosis (Shang et al, 2022). These findings suggest that our circRNA may also regulate mitochondria in OA, providing new research ideas.…”
Section: Circrna Is Involved In the Oxidation Stress Processmentioning
confidence: 77%
“…Both in vivo and in vitro experiments have demonstrated that CircFAM160A2 regulates chondrocyte mitochondrial stability and chondrocyte apoptosis through the miR-505-3p/SIRT3 axis (Bao et al, 2021). Recent studies have also that CircHIPK3, through the mir-30a-3p/PON2 axis, regulates mitochondrial function, which in turn affects chondrocyte apoptosis (Shang et al, 2022). These findings suggest that our circRNA may also regulate mitochondria in OA, providing new research ideas.…”
Section: Circrna Is Involved In the Oxidation Stress Processmentioning
confidence: 77%
“…The improvement in overall transmittance of the grown structure in the visible region that extended into the infrared region is observed when the InGaN layer was grown at 840°C. However, additional measurement and proof would be needed to explain this behavior, as the optical transmittance is also affected by surface scattering and impurity absorption (Wang et al , 2018a).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the gallium and indium adatoms are more easily to achieve thermodynamic steady state, and the interfaces become flat and steep. Moreover, in the mixed gas environment of H 2 and NH 3 , indium-rich clusters will desorb more easily than the indium-poor regions [ 31 ]. Thus, the distribution of indium content will be more uniformly across the whole well layers, resulting in a better MQWs’ homogeneity of sample B.…”
Section: Resultsmentioning
confidence: 99%